Biochemistry - Berg, Jeremy M; Tymoczko, John L.; Stryer, Lubert (New York: W. H. Freeman and Company, 2012)
The seventh edition has been updated throughout, including many new advances on genetic regulation, and revamped coverage of the integration of metabolism in the context of diet and obesity. Numerous new medical examples have been added throughout to make biochemistry real and relevant to students. The addition of new contributing author Gregory Gatto, an active pharmaceutical researcher at GlaxoSmithKline, ensures that the seventh edition presents the latest techniques that students need to understand in biochemistry research today. The end-of-chapter problems have also been revised and updated, providing students with great new exercises to test their understanding.
Index B1-B48 p.
Keywords: Biochemistry; Chemistry; General Science